ANALYTICAL REVIEW OF THEORETICAL PHASE OF PSYCHOLOGICAL TOOLS DEVELOPMENT – METAPHORICAL ASSOCIATIONAL CARDS "MASC" FOR THE PURPOSE OF RESEARCH OF SERVICEMEN (COMBATANTS) OF THE ARMED FORCES OF UKRAINE - Kravchenko, K.; Kravchenko, K.; Sokolina, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article presents analytical review of theoretical phase of psychological techniques development – metaphorical association cards "Masc" to work with servicemen (combatants) of the Ukrainian armed forces. The main purpose of the tools abovementioned is to increase efficiency of psychological support of servicemen (combatants) of the Ukrainian armed forces (including those who take part in combat actions in the combat area). Metaphorical association cards provide arrangement of constructive dialog between a serviceman and a psychologist that makes possible to optimise time for getting into psychological contact. Metaphorical associational cards are helpful both in performing of psychognosis of servicemen (individually and in groups) promptly and enabling to resolve numerous problems (normalize negative emotional conditions, increase motivation for activity, contribute to resolve conflict situations inside of unit) etc. Use of these cards is more practical because of massive refusals of servicemen to perform tests’ tasks with traditional methods of psychognosis, i.e. survey, blank test procedures, computer-based automated psychological procedures, etc. The following results were obtained from theoretical phase of research: 1) peculiarities of metaphorical associational cards were defined, they were recognised as an active psychological tool. Procedure for their employment was determined. Basic recommendations for their development were formed; 2) particularities and advantages of Masc therapy method were defined, and recommendations for it practical use were developed; 3) advantages of both methods combination – Masc therapy method and metaphorical associational cards (MAC) use were established. Creation of psychological tools MAC "Masc" was the result of this research, it is designed for psychological work with servicemen (combatants) of the Armed Forces of Ukraine; 4) the basic list of problems was defined, that is the object to find solution for them by mean of abovementioned psychological tools. It is based on analytical description of part-time groups of psychological aid that accompany Ukrainian Armed Forces units in the battle area from the beginning of full-scale invasion; 5) the procedure for development of metaphorical association cards for psychological work with combatants of Ukrainian armed forces was created.